TOR Inhibitors Synergistically Suppress the Growth and Development of Phytophthora infestans, a Highly Destructive Pathogenic Oomycete - Zhang, Shumin; Khalid, A. Rehman; Guo, Dongmei; Zhang, Jingping; Xiong, Fangjie; Ren, Maozhi (Frontiers in Microbiology, 2021)
Phytophthora infestans, one of most famous pathogenic oomycetes, triggered the Great Irish Famine from 1845 to 1852. The target of rapamycin (TOR) is well known as a key gene in eukaryotes that controls cell growth, survival and development. However, it is unclear about its function in controlling the mycelial growth, sporulation capacity, spore germination and virulence of Phytophthora infestans. In this study, key components of the TOR signaling pathway are analyzed in detail. TOR inhibitors, including rapamycin (RAP), AZD8055 (AZD), KU-0063794 (KU), and Torin1, inhibit the mycelial growth, sporulation capacity, spore germination, and virulence of Phytophthora infestans with AZD showing the best inhibitory effects on Phytophthora infestans. Importantly, compared with a combination of RAP + KU or RAP + Torin1, the co-application of RAP and AZD show the best synergistic inhibitory effects on P. infestans, resulting in the reduced dosage and increased efficacy of drugs. Transcriptome analysis supports the synergistic effects of the combination of RAP and AZD on gene expression, functions and pathways related to the TOR signaling pathway. Thus, TOR is an important target for controlling Phytophthora infestans, and synergism based on the application of TOR inhibitors exhibit the potential for controlling the growth of Phytophthora infestans.